2005
DOI: 10.1016/s0002-9440(10)62340-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interleukin-27 (EBI3/p28) Expression in Epstein-Barr Virus- and Human T-Cell Leukemia Virus Type 1-Associated Lymphomas

Abstract: Interleukin (IL)-27 is a novel heterodimeric cytokine of the IL-12 family that is composed of two subunits, Epstein-Barr virus (EBV)-induced gene 3 (EBI3) and p28. EBI3 is expressed at high levels in EBV-transformed B-cell lines and is induced in vitro by the EBV oncogene LMP1 in a nuclear factor (NF)-kappaB-dependent manner. We show here that EBI3 expression is up-regulated in human T-cell leukemia virus type 1 (HTLV-1)-infected cell lines and IL-2-dependent leukemic cells from adult T-cell leukemia/lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 40 publications
4
59
0
1
Order By: Relevance
“…In a previous study, we showed that low levels of EBI3 could be induced in human T cells upon in vitro stimulation with PHA and IL-2 (14). Therefore, to further analyze the expression of EBI3 in human T cells, whole CD4 ϩ T cells or subsets of naive or memory CD4 ϩ T, Treg, and Teff cells were stimulated for 2 days with beads coated with anti-CD3 and anti-CD28 Abs (a more physiological stimulus than PHA) in the absence or presence of IL-2, and cell lysates were analyzed for EBI3 expression by immunoblotting (Fig.…”
Section: Analysis Of Ebi3 Expression In In Vitro-stimulated Cd4 ϩ T Cmentioning
confidence: 97%
“…In a previous study, we showed that low levels of EBI3 could be induced in human T cells upon in vitro stimulation with PHA and IL-2 (14). Therefore, to further analyze the expression of EBI3 in human T cells, whole CD4 ϩ T cells or subsets of naive or memory CD4 ϩ T, Treg, and Teff cells were stimulated for 2 days with beads coated with anti-CD3 and anti-CD28 Abs (a more physiological stimulus than PHA) in the absence or presence of IL-2, and cell lysates were analyzed for EBI3 expression by immunoblotting (Fig.…”
Section: Analysis Of Ebi3 Expression In In Vitro-stimulated Cd4 ϩ T Cmentioning
confidence: 97%
“…In mouse or human primary cultures in vitro, IL-27 was found to be primarily expressed by activated monocytes and monocyte-derived dendritic cells, whereas in human tissues EBI3 and p28 coexpression was predominantly observed in macrophages or macrophage-derived cells and in endothelial cells (2)(3)(4). IL-27 receptor complex comprises two ␤-chains, IL-27R (also called WSX-1 or TCCR) and gp130 (2,5).…”
Section: Differential Effects Of Il-27 Onmentioning
confidence: 99%
“…In comparison with wild-type mice, WSX-1 (-/-) mice manifest significantly increased levels of airway immune response and serum IgE with infiltration of the pulmonary eosinophil, indicating that IL-27 and WSX-1 have a function in the down-regulation of airway hyper-reactivity and lung inflammation during the development of allergic asthma (Miyazaki et al 2005). The dissociated expression of EBI3 and p28 in transformed cells suggests that EBI3 may play a role -independent of its association with p28 -in the regulation of anti-viral and anti-tumoral responses (Larousserie et al 2005).…”
Section: Introductionmentioning
confidence: 99%